2015
DOI: 10.1002/2014ja020943
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric ionospheric outflow observed at the dayside magnetopause

Abstract: An important source of the terrestrial magnetospheric plasma is the Earth's ionospheric outflows from the high-latitude regions of both hemispheres. The ionospheric ion outflows have rarely been observed at the dayside magnetopause. We report Cluster observations of the ionospheric ion outflows observed at the dayside magnetopause. The low-energy (up to 1.5 keV) electrons are detected with bidirectional pitch angle distributions indicating that the magnetic field lines are closed. The unidirectional cold ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015]. The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015].…”
Section: Events Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015]. The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015].…”
Section: Events Overviewmentioning
confidence: 99%
“…Two Cluster magnetopause encounters are presented. The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015]. [Balogh et al, 2001].…”
Section: Events Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms for generation of the cold plasmas in the dayside magnetosphere have been proposed as the plasmaspheric drainage plume [Borovsky and Denton, 2008] and direct ionosphere outflow [Lee et al, 2015]. Han et al [2015] found that DDAs in stripy form, approximately aligned in north-south direction, are frequently observed near MLN and suggested that stripy DDAs should be mapping to wedge-like cold plasma structures extending from low to high L shells in the dayside magnetosphere.…”
Section: Dayside Diffuse Auroras and The Cold Plasmas Originated Frommentioning
confidence: 99%